Demographic Characteristics Influencing Knowledge Regarding Resources Available for Prevention of Suicide among College of Medical Science Students at the University of Guyana - Vanlewin, Obena; Hutson, Andrew; Abrams, Charlan; Boston, Cecil; Cecil, Deborah (Asian Journal of Medicine and Health, 2025)
Background: Suicide remains a pressing global public health issue, particularly as the second leading cause of death among 15–29-year-olds. Family structure and geographical location are hypothesized to impact awareness, knowledge, and access to suicide prevention resources, influencing overall mental health literacy. Subjects: This study involved 243 students from the College of Medical Science at the University of Guyana. The sample was predominantly female (83.5%), with a mix of undergraduate (81.5%) and postgraduate students. Methods: An analytical cross-sectional survey using a modified suicide knowledge and skills questionnaire was employed to examine the relationships between residence type (rural, suburban, urban), parental marital status (married/living together vs. other), and knowledge of suicide resources, as assessed by a 5-point Likert Scale. Data was analyzed using chi-square tests and Fisher's Exact Test, with post-hoc power analysis. Results: A statistically significant association was found between parental marital status and knowledge of resources (p = .005). Participants with parents not married or living together showed a trend toward greater knowledge of resources. There was a marginally significant association between residence type and knowledge of resources (p = .055). Conclusion: These findings underscore the intricate factors influencing mental health literacy in the Caribbean, specifically in Guyana. Interventions aimed at suicide prevention should be culturally tailored to address the unique needs of students from diverse family and residential backgrounds and should address the potential influence of cultural stigma. Further research is needed to explore the reasons behind the unexpected relationship between parental marital status and resource knowledge.